2009
DOI: 10.1136/ard.2008.102624
|View full text |Cite
|
Sign up to set email alerts
|

Junctional adhesion molecule-A is abnormally expressed in diffuse cutaneous systemic sclerosis skin and mediates myeloid cell adhesion

Abstract: Objective-To investigate the role of Junctional adhesion molecule A (JAM-A) in the pathogenesis of systemic sclerosis (SSc).Methods-Biopsies from proximal and distal arm skin and serum were obtained from patients with SSc and normal (NL) volunteers. To determine the expression of JAM-A on SSc dermal fibroblasts and in SSc skin, cell surface ELISAs and immunohistology were performed. An ELISA was designed to determine the amount of soluble JAM-A (sJAM-A) in serum. Myeloid U937 cell-SSc dermal fibroblast and ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 22 publications
4
19
4
Order By: Relevance
“…Having observed a similar inflammatory-induced alteration of cell-bound JAM-A expression as previously described in non-CNS EC types, we next investigated whether HBMEC show a basal or inducible release of sJAM-A as previously described in HUVEC and HDMEC [22], [23]. To measure sJAM-A, we developed a sandwich ELISA.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Having observed a similar inflammatory-induced alteration of cell-bound JAM-A expression as previously described in non-CNS EC types, we next investigated whether HBMEC show a basal or inducible release of sJAM-A as previously described in HUVEC and HDMEC [22], [23]. To measure sJAM-A, we developed a sandwich ELISA.…”
Section: Resultsmentioning
confidence: 70%
“…In HUVEC, sJAM-A was found to be shedded from the cell surface by the disintegrin and metalloproteinases (ADAM) 10 and 17 upon pro-inflammatory stimulation [23]. On a functional level, recombinant sJAM-A reduced adhesion of mononuclear cells to cultured HUVEC and HDMEC [22], [24]. Furthermore it reduced chemokine-triggered endothelial transmigration of CD4 + CD45RO + memory T cells across HUVEC under static and flow conditions [24].…”
Section: Introductionmentioning
confidence: 99%
“…An immunohistochemical study in human arthritis has also demonstrated JAM-C expression on the synovial fibroblasts of both osteoarthritis and rheumatoid arthritis patients, in conjunction with JAM-C-dependent adhesion of myeloid cells to these fibroblasts (Rabquer et al, 2008). Enhanced expression of JAM-A has also been described on the skin of patients with the inflammatory disorder systemic sclerosis, in comparison to that on normal dermal fibroblasts (Hou et al, 2009). Aside from facilitating adhesion of leukocytic cells to stromal elements such as fibroblasts, another way in which JAM family members could influence the breast cancer microenvironment is by altering proliferation of fibroblasts or other accessory cells.…”
Section: Jam Proteins and The Regulation Of Stromal Cellsmentioning
confidence: 92%
“…sJAM-A is elevated in the serum of patients with SSc compared with healthy volunteers [33]. However, membrane-bound JAM-A is decreased on ECs in SSc skin [33]. Therefore, SSc ECs may be unable to mount an angiogenic response to sJAM-A.…”
Section: Systemic Sclerosis Angiogenic Receptor Dysregulationmentioning
confidence: 97%
“…sJAM-A promotes angiogenesis by interacting with membrane-bound JAM-A on the surface of ECs. sJAM-A is elevated in the serum of patients with SSc compared with healthy volunteers [33]. However, membrane-bound JAM-A is decreased on ECs in SSc skin [33].…”
Section: Systemic Sclerosis Angiogenic Receptor Dysregulationmentioning
confidence: 99%